ALAM SEBAGAI SUMBER ENERGI TERBARUKAN - Kelvin, Kelvin Khoidir; Muhammad Erik Raditya; Ardika Chandra Winata; Salman Alfarissi; Khairulduha, Khairulduha (Asosiasi Dosen Muda Indonesia, 2024)
Renewable energy can be made through an analysis process carried out by experts so that it becomes energy that is widely used by the wider community. And basically fossil energy has almost run out in this world so experts want to make new energy through the use of resources in nature so that fossil energy will be left behind and then energy in nature will be used to make new environmentally friendly energy such as electrical energy. Then the electrical energy will be used for the wider community as its function is the same as fossil energy so that the use of fossil energy will be abandoned slowly.